2019
DOI: 10.1007/s00392-019-01513-y
|View full text |Cite|
|
Sign up to set email alerts
|

The influence of atrial fibrillation on the levels of NT-proBNP versus GDF-15 in patients with heart failure

Abstract: Background In heart failure (HF), levels of NT-proBNP are influenced by the presence of concomitant atrial fibrillation (AF), making it difficult to distinguish between HF versus AF in patients with raised NT-proBNP. It is unknown whether levels of GDF-15 are also influenced by AF in patients with HF. In this study we compared the plasma levels of NT-proBNP versus GDF-15 in patients with HF in AF versus sinus rhythm (SR). Methods In a post hoc analysis of the index cohort of BIOSTAT-CHF (n = 2516), we studied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 29 publications
0
46
0
1
Order By: Relevance
“…Similar results were observed in patient with acute coronary syndrome (ACS) [6], stable coronary artery disease (CAD) [7], and high risk population [8]. Inconsistently, BIOSTAT-CHF trial has reported that GDF-15 levels were not in uenced by the presence of atrial brillation (AF) in patients with heart failure (HF) [9]. Since those observational studies inevitably blend with some confounding factors (where some factors associated with GDF-15 actually result in the disease) and reverse causality bias (where some patients with CVD may be more likely to higher GDF-15), it remains controversial whether GDF-15 is causally associated with the incidence of CVD.…”
Section: Many Different Mechanisms Beyond Glycemic Control Have Been mentioning
confidence: 59%
See 1 more Smart Citation
“…Similar results were observed in patient with acute coronary syndrome (ACS) [6], stable coronary artery disease (CAD) [7], and high risk population [8]. Inconsistently, BIOSTAT-CHF trial has reported that GDF-15 levels were not in uenced by the presence of atrial brillation (AF) in patients with heart failure (HF) [9]. Since those observational studies inevitably blend with some confounding factors (where some factors associated with GDF-15 actually result in the disease) and reverse causality bias (where some patients with CVD may be more likely to higher GDF-15), it remains controversial whether GDF-15 is causally associated with the incidence of CVD.…”
Section: Many Different Mechanisms Beyond Glycemic Control Have Been mentioning
confidence: 59%
“…Furthermore, serum GDF-15 level was associated with incident AF with the hazards ratios of 1.31 after adjusted for age and gender [30]. However, some inconsistent studies showed that serum GDF-15 level was not in uenced by the presence of AF in patient with HF from the BIOSTAT-CHF trial [9] and patients with chronic kidney disease (CKD) from the CRIC study [34]. Potential pathologic mechanisms of AF include atrial remodeling, reentry, pulmonary vein trigger, abnormal autonomic nerve modulation and in ammation.…”
Section: Gdf-15 and Afmentioning
confidence: 99%
“…Similarly, GDF-15 was reckoned independently associated with paroxysmal AF after multivariable analyses in a study where a signi cantly higher serum level of GDF-15 was found in patients with paroxysmal AF than controls (1473.14 ± 628.52 vs. 1233.592 ± 262.76 pg/ml, P < 0.05) [28]. In contrast, Santema BT, et al and Lamprea-Montealegre JA, et al suggested that serum GDF-15 level was undifferentiated with AF or not in folks with HF from BIOSTAT-CHF trial [29] and people with chronic kidney disease(CKD) from CRIC study [30] respectively. Dissimilitude could have been explained for speci c reasons.…”
Section: Discussionmentioning
confidence: 96%
“…NT-proBNP düzeylerinin AF'da yüksek olduğu bilinmekle beraber, bu yükselmenin ne kadarından AF'un, ne kadarından KY'nin [11,19]. Bizim çalışmamızın literatüre en önemli katkısı, NP üst sınırı için bir konsensus olmayan DEF-KY ve AF bulunan hastalarda (eşlik eden ılımlı böbrek yetmezliği ile beraber), stabil kronik fazdaki ortalama NT-proBNP düzeyleri ile ilgili bir fikir vermesi, bu hastalarda dekompansasyon tanısı için standart üst sınırların yeterli olmadığını düşündürmesidir.…”
Section: Gereç Ve Yöntemunclassified